Cost-effectiveness and cost-utility of hypertension and hyperlipidemia collaborative management between pharmacies and primary care in portugal alongside a trial compared with usual care (USFarmácia®) - Costa, Suzete (2022)
Funding Information: The trial was promoted by the NHS Group of Primary Care Units [Agrupamento dos Centros de Saúde, or ACeS] of Baixo Mondego Region and the Portuguese National Association of Pharmacies [Associação Nacional das Farmácias, or ANF] and was funded by ANF. Study promoters and funders had no role in the design and conduct of the trial/study; collection, management, analysis, and interpretation of data; and writing, review, approval, or decision to submit this manuscript for publication. SC paid for the open access publication fee for this manuscript. Publisher Copyright: Copyright © 2022 Costa, Guerreiro, Teixeira, Helling, Pereira and Mateus.